TRANSFORMASI PERAN GURU PAI SEBAGAI SPIRITUAL COUNSELING DALAM MEWUJUDKAN WELL-BEING MURID DI ERA DISRUPSI - Rustam, Rustam; Ilham, Ilham (Kreatif: Jurnal Pemikiran Pendidikan Agama Islam, 2026)
The era of disruption, characterized by rapid technological advancement and social changes, presents significant challenges to the spiritual, emotional, and moral development of students. This condition demands a transformation in the role of Islamic Religious Education (PAI) teachers, who must not only function as educators transferring knowledge but also as spiritual counselors capable of guiding students in navigating life’s dynamics. This study aims to describe the strategic role of PAI teachers in promoting student well-being, which encompasses spiritual, emotional, social, and moral aspects in the disruptive era. The method used is a literature study by analyzing various references related to the concepts of well-being, spiritual guidance, and the contemporary competencies of PAI teachers. The findings indicate that PAI teachers play an essential role in shaping Islamic character, providing psychosocial and spiritual support, and creating a supportive learning environment through Islamic counseling approaches. This transformed role can be implemented through strengthening teachers’ spiritual, pedagogical, and social competencies, utilizing technology in learning, and establishing collaboration with parents and the school environment. Thus, PAI teachers are expected to become role models who facilitate students’ holistic development toward the achievement of well-being amid the challenges of the disruptive era. Keywords: PAI Teachers, Spiritual Counseling, Well-being, Disruptive Era, Characucationter Ed